Leviticus and Numbers - Bellinger, W. H. (William H.), Jr., 1949-; Jr. W.H. Bellinger (Grand Rapids, Mich. : Baker Books, 2012)
"This volume takes on two oft-neglected books of Scripture with the conviction that modern believers can gain much benefit from them. Amid the laws and lists, these two books display the holiness and awesomeness of God, the importance of purity, the nature of worship, the importance of obedience, and the consequences of disobedience in the early life of Israel." -- Publisher's description
Originally published: Peabody, Mass. : Hendrickson Publishers ; Carlisle, Cumbria, U.K. : Paternoster Press, c2001
Includes bibliographical references (p. [323]-325) and indexes
Keywords: Bible. -- Commentaries; Bible. -- Commentaries